Nilai Pendidikan Agama Hindu Dalam Pementasan Tarian Sang Hyang Jaran Di Banjar Palarejo Desa Ekasari Kecamatan Melaya Kabupaten Jembarana - I Komang Arta Suyasa; I Wayan Madra; Ida Ayu Adi Armini (Jayapangus Press, 2019)
Implementation of religious ceremonies (piodalan) in Bali always include a form of art in it, one of which is a guardian dance. There are many types of guardian dance performed in a piodalan one of them Sang Hyang dance. Of the many dance the hyang Sang Hyang Jaran dance is a dance chosen by masyaraat nusa penida who settled in Banjar Palarejo Ekasari Village as a guardian dance performed at Pandean banjar Palerejo Temple. It is above the background of researchers to conduct scientific research. The problems discussed are; (1) The form of staging dance Sang Hyang Jaran in Banjar Palarejo Village Ekasari Melaya District Jembrana? (2) Sang Hyang Jaran dance function in Banjar Palarejo Desa Ekasari Melaya District Jembrana District? (3) The value of Hindu Religion education contained in Sang Hyang Jaran Dance in Banjar Palarejo Desa Ekasari Melaya Sub-district Jembrana District? This study aims to determine (1) The form of staging Dance Sang Hyang Jaran in Banjar Palarejo Village Ekasari Melaya District Jembrana District (2) Function staging Dance Sang Hyang Jaran in Banjar Palarejo Village Ekasari Melaya District Jembrana District (3) The value of pendidian Hindu religion in Sang Hyang Jaran Dance at Banjar Palarejo Desa Ekasari Melaya Sub-district Jembrana District. The theory used to analyze the problem is; Religious theory, structural functional theory, value theory. This type of research is qualitative. This research was conducted in August to November in Ekasari Village, Melaya District, Jembrana District.The results of this study indicate that Sang Hyang Jaran dance in Banjar Palarejo Desa Pekraman Ekasari is a dance that is sacred, if not danced can cause life imbalance. The staging process is traversed by several stages: nyudi, nusdus, dancing and returning consciousness of the dancer. The function of this dance performance is rejecting reinforcement, as a unifying tool of society, the function of cultural art preservation. The value of Hindu Religious Education contained in the dance Sang Hyang Jaran is tattwa value, moral value, aesthetic value. Sang Hyang Jaran Dance is believed to be a symbol of God's descent to earth as a symbol of sanctification.